Ei gostosa! Assédio de rua e interações no espaço público - Savio, Thaynã Davilla (2016)
This dissertation s main objective is to analyze street harassment as a violation of social rules, and also its negative effects in the life of harassed women. Despite changes in relationships between men and women and the conquest rights directed to women, street harassment remains a common practice. Street harassment is studied from women s perspective as an undesirable interaction in public spaces, that shows the different ways men and women occupy this space. The argument presented is the glamorization of street harassment, the reinforcement of masculinity and the relationships between harasser and the harassed female that coexist with incresing critics from the media and from women. Street harassment is, therefore, analyzed as a tension between the reputed juridical equality and gender performativity, which is experimented through ambiguities. Synthetizing, street harassment is, at the same time, a violation of civil inattention rules e and an intensification of gender performativity. The data for the research was obtained through bibliographic sources, questionnaires applied in 97 students from a superior education institution and other sources obtained in the internet and social networks like facebook.